Application of Higuchi's fractal dimension from basic to clinical neurophysiology: A review. Issue 133 (September 2016) - Kesić, Srdjan; Spasić, Sladjana Z.
Highlights: The article reviews the applications of Higuchi's fractal dimension (HFD) in basic and clinical neurophysiology. This article summarizes and critically reviews a broad literature and major findings concerning the applications of HFD. Many studies on the presented topics demonstrated the advantage of HFD for measuring the complexity of neuronal activity. Abstract: Background and objective: For more than 20 years, Higuchi's fractal dimension (HFD), as a nonlinear method, has occupied an important place in the analysis of biological signals. The use of HFD has evolved from EEG and single neuron activity analysis to the most recent application in automated assessments of different clinical conditions. Our objective is to provide an updated review of the HFD method applied in basic and clinical neurophysiological research. Methods: This article summarizes and critically reviews a broad literature and major findings concerning the applications of HFD for measuring the complexity of neuronal activity during different neurophysiological conditions. The source of information used in this review comes from the PubMed, Scopus, Google Scholar and IEEE Xplore Digital Library databases. Results: The review process substantiated the significance, advantages and shortcomings of HFD application within all key areas of basic and clinical neurophysiology. Therefore, the paper discusses HFD application alone, combined with other linear or nonlinear measures, or as a part of automated methods for analyzing neurophysiological signals. Conclusions: The speed, accuracy and cost of applying the HFD method for research and medical diagnosis make it stand out from the widely used linear methods. However, only a combination of HFD with other nonlinear methods ensures reliable and accurate analysis of a wide range of neurophysiological signals.